Professional Self-Efficiency and Subjective Success of Managers at Different Levels - Seliverst, Maxim; Turenko, Rimma (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2024)
The purpose of our work was to determine the characteristics of the relationship between professional self-efficacy and subjective success in managers of different levels who work in Ukrainian companies during the war in Ukraine. Managers of different levels (N=58) participated in the study, who were involved in the study through various online platforms. Among the subjects - 43 men and 15 women aged 27 to 56 years. Research methods: questionnaire, numerical scaling, questionnaire of professional self-efficacy ("Short occupational self-efficacy scale"), "Who am I?" method. M. Kuhn and T. McPartland. The managers under study have a high level of subjective success, which is moderately high and indicates the satisfaction of the subjects with their own achievements and behavior. The professional self-efficacy of the managers under study has a moderately high value. Managers clearly formulate goals in their work and feel motivated to overcome all obstacles that stand on the way to a certain result. The identity of different levels managers researched is presented as follows: in the first place there is the professional role position (leader, entrepreneur, manager and specialist), then - family affiliation and roles in the family (husband, father, son, brother), personal qualities (reliability, stability , justice, sincerity, diligence), characteristics of activity ("study an interesting topic", "make your friends happy") complete the list of friendship criteria, existential self, self-assessment of social skills, description of your physical data, citizenship, ethnic and gender identity. Managers who have a larger number of subordinates, are close to the head of the company, and have a high level of professional self-efficacy, are more likely to consider themselves completely successful.